The consensual politics of development: a case study of hydropower development in the eastern Himalayan region of India - Joshi, Deepa; Platteeuw, J.; Teoh, J. (2019)
Criticism and contestation of large dam projects have a long, strong history in India. In this paper, we analyze diverse civil-society responses to large dam projects in the Eastern Himalaya region of India, which has in the past decades been presented as a clean, green, climate-mitigating way of generating energy, but critiqued for its adverse impacts more recently. We draw our findings primarily based on interviews with NGOs involved in environmental and/or water issues in Darjeeling, interviews with those involved in a local people’s movement ‘Affected Citizens of Teesta’, and participatory research over the course of three years between 2015 and 2018. Our findings show how doing development for the state, the market and/or donor organizations compromises the ability of NGOs in the Darjeeling region to hold these actors accountable for social and environmental excesses. In the same region, dam projects in North Sikkim led to a local people’s movement, where expressions of indigeneity, identity and place were used to critique and contest the State’s agenda of development, in ways that were symptomatically different to NGOs tied down by relations of developmental bureaucracy. Our findings reveal how the incursion of State authority, presence and power in civil-society undermines the civil society mandate of transformative social change, and additionally, how the geographical, political, institutional and identity-based divides that fragment diverse civil-society institutions and actors make it challenging to counter the increasingly consensual politics of environmental governance.